Regarding the article “Irrational fixed dose combinations in Nepal: Need for intervention” (KUMJ, Vol 6, No. 3, Issue 23, p. 399-405) - Poudel, A; Khanal, S; Alam, K; Palaian, S (Kathmandu University Medical Journal, 2009)
doi: 10.3126/kumj.v6i4.1753     Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 537-538